2009
DOI: 10.1111/j.1471-0528.2009.02194.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal ultrasound to predict postnatal renal function in congenital lower urinary tract obstruction: systematic review of test accuracy

Abstract: Background Congenital urinary tract obstruction can lead to perinatal mortality and morbidity. Assessing antenatal ultrasound features may help identify fetuses likely to suffer complications.Objective To evaluate the accuracy of antenatal ultrasound in the prediction of postnatal renal function in cases of congenital lower urinary tract obstruction (LUTO). Data collection and analysis Data were extracted on study characteristics, quality and results to construct 2 · 2 tables.Likelihood ratios for positive (LR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(110 citation statements)
references
References 48 publications
4
97
0
4
Order By: Relevance
“…The high costs incurred were almost entirely due to prolonged NICU admission immediately after birth in these infants (data not shown). It is possible that these infants would have succumbed to LUTO in the absence of VAS (the infants with 'poor prognosis' on antenatal scans 70 ). These children continued to have higher admission rates in the first year (beyond the neonatal period) and are responsible for the higher costs in the VAS arm relative to the conservative arm.…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The high costs incurred were almost entirely due to prolonged NICU admission immediately after birth in these infants (data not shown). It is possible that these infants would have succumbed to LUTO in the absence of VAS (the infants with 'poor prognosis' on antenatal scans 70 ). These children continued to have higher admission rates in the first year (beyond the neonatal period) and are responsible for the higher costs in the VAS arm relative to the conservative arm.…”
Section: Probabilistic Sensitivity Analysismentioning
confidence: 99%
“…This is in all likelihood because evaluation of this diagnostic test has indicated that it has little value over assessment of renal appearance and liquor volume. 14,70 It was also interesting to note the number of antenatally identified babies with LUTO who were potentially amenable to 'in utero' therapy. Of the prenatally suspected, isolated, singleton male LUTO cases, 2% underwent serial vesicocentesis and 8% underwent VAS.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may have an important impact for prenatal counseling. However, postnatal kidney function is difficult to predict based on ultrasound studies, especially the long-term outcome [4,5]. Magnetic resonance imaging scans can provide additional information on fetal urinary tract abnormalities in some cases, but these have not been evaluated as a modality to predict postnatal outcome [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In one study of fetal hyperechogenic kidneys (mostly due to ARPKD), the presence of ROH and a kidney size of >4 standard deviations (SD) had a negative impact on outcome [17]. Morris et al [18] performed a systematic review that included 215 pregnancies with ultrasound evidence of congenital LUTO in which they evaluated the accuracy of fetal ultrasound to predict postnatal renal function. Any described ultrasound parameter was considered in the analysis (i.e.…”
Section: Antenatal Imaging Of the Fetal Urogenital Tract And Lungsmentioning
confidence: 99%